Variation in Severity of Symptoms Associated With Two Snow Mountain Virus Inocula - Qu, Hongyan; Rouphael, Nadine; Mulligan, Mark; Wang, Yuke; Sablon, Orlando; Moe, Christine L.; Liu, Pengbo (Journal of medical virology, 2025)
ABSTRACT Snow Mountain Virus (SMV), the prototype of genogroup II and genotype II Norovirus (NoV), was used in human challenge studies to examine the infectivity, pathogenicity, and immune response to NoV. Clinical and laboratory data from two previously completed SMV human challenge trials using two different inocula (primary and secondary) were analyzed to compare the infectivity, illness, viral shedding, and serum IgG conversion. The primary and secondary SMV inocula were sequenced for detecting single nucleotide mutations. Of 15 subjects challenged with the primary inoculum between 2000 and 2002, nine were infected, and seven presented with acute gastroenteritis. Of 33 subjects challenged with the secondary inoculum between 2016 and 2018, 25 were infected, and nine presented with acute gastroenteritis. There were no statistically significant differences in overall infection and illness rates between subjects challenged with the primary inoculum versus the secondary inoculum. However, subjects infected with the primary inoculum experienced more severe clinical symptoms of acute gastroenteritis, showing higher severity scores (6.00 vs. 2.94, p = 0.003) compared with those infected with the secondary inoculum. We also observed that infection with the secondary inoculum resulted in longer viral shedding compared with the primary inoculum. Partial sequencing of the SMV genome identified three mutations in both inocula. Understanding the differences between these two SMV inocula is critical for NoV vaccine evaluation and using a less pathogenic inoculum for a vaccine trial will require more participants to meet the target reduction in illness when evaluating the efficacy of candidate vaccines.